Analisis Wacana Representasi Budaya dan Ideologi dalam Film Wadjda (2012) Pendekatan Semiotika Roland Barthes - Ridwan Agustiawan (AL MA'ANY, 2024)
This study aims to analyze the film Wadjda (2012) through discourse analysis using Roland Barthes' semiotic perspective. Wadjda, directed by Haifaa al-Mansour, is a Saudi Arabian film that tells the story of a young girl named Wadjda who strives to own a bicycle as a symbol of freedom and rebellion against prevailing social norms. Using Barthes' semiotic approach, this research examines the signs and symbols present in the film to uncover the meanings embedded in its visual and narrative elements. In the semiotic context, the analysis utilizes two levels of interpretation: the denotative level (literal meaning) and the connotative level (deeper or implied meaning). Key elements analyzed include the characters, objects (such as the bicycle), and the setting, all of which reflect the social and cultural structures of Saudi Arabia, particularly concerning gender roles, freedom, and women's position in society. Through the deconstruction of these signs, this study reveals how the film portrays contradictions within a patriarchal society and how these representations provoke critical reflection on existing norms. The findings show that Wadjda functions not only as an individual story about personal achievement but also as a critique of social injustices and gender restrictions in Saudi society. By employing Barthes' semiotic theory, the film uncovers how hidden meanings can be deconstructed to understand the relationship between cultural texts and the underlying social ideologies. This study contributes to the understanding of how film media can serve as an effective tool for social critique.